Zintegrowane informatyczne systemy zarządzania w przedsiębiorstwach produkcyjnych: Integrated information management systems in manufacturing companies - Klimek, Michał; Toruński, Janusz (Management and Administration Journal, 2021)
This paper presents the viewpoints of its Authors about the integration of the Integrated Information Management Systems in production enterprises. They explained first of all, the meaning of the main terms, as well as the role, and the integration process itself. Summary findings indicate the effective impact on the qualitative aspects, brought by the systems deployed in manufacturing companies.